The effects of relationship enrichment program on compatibility and marital satisfaction of infertile couples - Mohammad Reza Miri; Maryam Alizadeh; Narges Moasheri; Marzeyeh Ataee; Mitra Moodi (Mashhad University of Medical Sciences, 2016)
Background and objective: Infertility as a crisis in couples' life, not only creates psychological problems, but also, it can act as a powerful impact on the relationships between couples. The purpose of this paper is to study the effects of relationship enrichment on compatibility and marital satisfaction of infertile couples. Methods: This is a semi experimental study with pre-test and post-test on control group. Statistical population of this study was an infertile couple in Birjand. The couples were randomly divided to control groups (17 couples) and experimental groups (15 couples). The research instrument was marital adjustment questionnaire. That completed before, immediately and 3 months after intervention. The intervention consisted of 6 training session. Data were analyzed using SPSS software (version 16). Results: Before the intervention, mean scores were matched the two groups. After the intervention, the experimental group increased average compatibility from 101.5±22/4 to 129.33±10.6 , marital satisfaction from 33/8±8 to 44±4.8 , marital solidarity from12±3.8 to 16.1±2.2 , couples agreement from 44.6±10.5 to 54.8±6.1 , expression of love from 11±3.7 to 14.2± 1.(p